Phenotypes, bedside examination, and video head impulse test in vestibular migraine of childhood compared with probable vestibular migraine and recurrent vertigo in childhood - Teggi, Roberto; Colombo, Bruno; Familiari, Marco; Cangiano, Iacopo; Bussi, Mario; Filippi, Massimo (Frontiers in Pediatrics, 2023)
Vestibular impairment and vertigo in the pediatric population have an estimated prevalence ranging between 0.4% and 5.6% and are a topic of interest in recent years. The Bárány Society has recently reclassified migraine-related vertigo syndromes as vestibular migraine of childhood (VMC), probable vestibular migraine of childhood (probable VMC), and recurrent vertigo of childhood (RVC). Applying the criteria established by the Bárány Society, we retrospectively analyzed data on 95 pediatric patients suffering from episodic vertigo that were recruited from 2018 to 2022. In applying the revised criteria, 28 patients had VMC, 38 had probable VMC, and 29 had RVC. Visuo-vestibular symptoms (external vertigo) or internal vertigo were reported by 20 of 28 VMC patients (71.4%) compared to 8 of 38 probable VMC patients (21%) (P<.001). None of the RVC patients reported external vertigo. Duration of vertigo was demonstrably longer in the VMC patients than in the probable VMC (P<.001) and RVC (P<.001) patients. Cochlear symptoms were reported by 28.6% of VMC patients and by 13.1% of probable VMC patients. No cochlear symptoms were reported by any RVC patients. Familial cases for headache and episodic vertigo showed no significant difference between groups. The most frequent finding during bedside examination in all three groups was central positional nystagmus. Differences in the duration of attacks and in accompanying symptoms may underline different pathophysiological mechanisms.